Effects of ozone, chlorine dioxide, chlorine, and monochloramine on Cryptosporidium parvum oocyst viability. - Korich, D G (1990)
Purified Cryptosporidium parvum oocysts were exposed to ozone, chlorine dioxide, chlorine, and monochloramine. Excystation and mouse infectivity were comparatively evaluated to assess oocyst viability. Ozone and chlorine dioxide more effectively inactivated oocysts than chlorine and monochloramine did. Greater than 90% inactivation as measured by infectivity was achieved by treating oocysts with 1 ppm of ozone (1 mg/liter) for 5 min. Exposure to 1.3 ppm of chlorine dioxide yielded 90% inactivation after 1 h, while 80 ppm of chlorine and 80 ppm of monochloramine required approximately 90 min for 90% inactivation. The data indicate that C. parvum oocysts are 30 times more resistant to ozone and 14 times more resistant to chlorine dioxide than Giardia cysts exposed to these disinfectants under the same conditions. With the possible exception of ozone, the use of disinfectants alone should not be expected to inactivate C. parvum oocysts in drinking water.